Черная смерть: роман / Иван Стрельцов - Стрельцов Иван Захарович (Морпех, 2004)
Экземпляры: ф.4 (20151119) / Инвентарный номер: 2443 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: С 84 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44